EFEKTIVITAS MEDIA PITA GARISBILANGAN DALAM MENINGKATKAN KEMAMPUAN PENJUMLAHAN BAGI ANAK TUNAGRAHITA RINGAN KELAS DIV/C di SLB LIMAS PADANG - Susanti, Markis Yunus, Mega Iswari (Universitas Negeri Padang, 2013)
This study has problems that a child DIV class mild mental retardation / C in SLB Limas Padang, have difficulty in learning mathematics, especially in the sum of one-digit number series aside the results under 20. Under these conditions, this study aims to demonstrate the effective number line tape media in enhancing the ability of the sum of the digits are laterally series result for children under 20 mild mental retardation. The design of this study with the method of single subject A-B-A Reaserch (SSR). Results of this study showed that the number line tape media is effective in improving the ability of the sum of the series aside one digit number with one digit that the outcome for children under 20 mild mental retardation.